A Study of the Business Model of Tencent Group - Myeong-Cheol Choi, Seung-Jin Kim, Xian-Fa Shang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the development of information technology, Many Internet enterprises have emerged rapidly, and to thrive in the face of fierce competition, it is vital for them to have efficient business models. These business models are a popular focus of research interest. At present, there is still no unified interpretation of the business model system of Internet enterprises. The existing theoretical research examines mainly individual enterprises; there are only a very few studies on the business models of platform enterprises. This study therefore aims to summarize the literature on the basis of existing theories combined with the enterprise reality, through a literature review and case study of the Tencent group of companies in China. This study explores the online trading platform for enterprises and its business model.It is instructive to correctly analyze the Internet business model of enterprises in the third party service platform enterprises.